EFEKTIFITAS RUMPUT LAUT UNTUK PENINGKATAN KADAR HEMOGLOBIN PADA IBU HAMIL - Gustiani, Ria; Qudratullah, Fyzria (LPPM STIKes Mitra Adiguna, 2025)
The World Health Organization (WHO) reports that the prevalence of pregnant women with iron deficiency is around 40%, this increases with increasing gestational age. Normal hemoglobin levels in pregnant women are 11 gr / mmHg. Anemia in pregnancy is mostly caused by iron deficiency. Prevention of anemia in pregnant women can be done in various ways, one of which is by consuming Seaweed. This study uses a literature review, namely a series of studies related to the method of collecting library data or research whose research objects are explored through various library information (books, encyclopedias, scientific journals, newspapers, magazines and newspapers). Based on the results of the literature review, it is known that Eucheuma sp seaweed is one of the foodstuffs that contain several compounds needed in hemoglobin synthesis such as iron, protein and vitamin B complex, Eucheuma sp is also a seaweed that can stabilize the number of red blood cells, white blood cells, and Hemoglobin. So it is very effective for increasing hemoglobin levels in pregnant women. With this research, it is hoped that it can increase insight for pregnant mothers to increase awareness of anemia in pregnant women.